Social network sites and protection of children in Malaysia and Singapore: a comparative analysis - Islam, Md. Zahidul (2019)
Social networks are online services delivered through the Internet which allow users to produce a public profile. These social networks assist capturing of personal data and information of the users and provide tools to interact with other users. Social Networks are also accessible via mobile devices (Facebook, twitter, and others) where children and young people are using these social networking sites all round the world. The easy access and open nature of the social network sites facilitates users with many positive aspects but at the same time it is vulnerable to the children in case of abusive parties. Obscenity, hate speech, and indecent contents that are not suitable for children are very common in the social network sites now a days. The Malaysian and Singapore government came forward to regulate these contents. However, the technology that controls this restriction can easily be evaded and the service providers are still in the dark regarding appropriate label contents which is accessible to the children. Both Governments and corporations agree that control is insufficient and so companies embark on self-regulation of themselves through Codes of Conduct. The objective of this paper is to compare how far the regulation and self-regulation protect children in social networks sites and what need to be done to improve the effectiveness of regulation. The researcher mainly adopted qualitative methods. The information has taken from many readings, articles, books, newspapers and statutes. The paper compares social networks in Malaysia and Singapore to find strengths and opportunities that could enrich regulation of social networks in those countries.